Macroeconomic Factors and Tax Revenue Performance in South Africa: A Markov-Switching Model Approach - Dumisani Pamba (International Journal of Management, Accounting and Economics, 2025)
Tax revenue is a key funding source for South Africa's government, essential for public services. However, it has been volatile in recent years. This study examines the macroeconomic factors influencing tax revenue performance in South Africa from 2000Q1 to 2023Q3, utilizing the Markov Switching Model (MSM). The results show that macroeconomic factors operate differently under varying economic conditions. Specifically, inflation and interest rates negatively impact tax revenue in regime 1, while they positively influence it in regime 2. In contrast, the exchange rate and current account balance positively affect tax revenue in regime 1 but negatively in regime 2. Economic growth consistently has a positive effect in both regimes. Overall, the findings highlight the need to consider economic conditions when evaluating tax revenue performance. Policymakers must account for these differing effects to develop effective tax policies that optimize revenue collection in South Africa. Understanding how various economic conditions influence tax revenue enables authorities to adjust their strategies for sustainable and consistent revenue generation